Aktivitas isosim glucose-6-phosphate dehydrogenase (G6PD) pada penderita glaukoma simpleks - A. Soemarsono A. Soemarsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Simple glaucomas are charaterized by an elevated intra ocular pressure (10P) and, are an important cause of blindness in the world. The blindness is due to the optic nerve atrophy and is found more frequently in women. It has been reported that high activity of G6PD isozyme can reduce the ocular pressure in the calf eyes. The activity of G6PD isozyme in the blood of simple glaucoma patients has been examined, and compared to those of normal persons. This study consisted of 76 patients of simple glaucoma (41 men and 35 women) and 30 normal persons as a control group. The 10P of both patients and control group was measured by using a Schiotz tonometer. The average of the G6PD isozyme activity was 9.40 ulg Hb in the simple glaucoma and 10.94 u/g Hb in control group. The two G6PD isozyme activity showed a significant difference. It can be concluded that the activity of G6PD isozyme of simple glaucoma patients were lower than those of normal persons without glaucoma symptoms.Key Words : isozyme - G6PD - glaucoma